Do employment factors reduce the effect of low education on mental health? A causal mediation analysis using a national panel study. (9th July 2018) - Milner, Allison; Blakely, Tony; Disney, George; Kavanagh, Anne M; LaMontagne, Anthony D; Aitken, Zoe
Abstract: Background: Young people with low education have worse health than those with higher education. This paper examined the extent to which employment and income reduced the adverse effects of low education on mental health among people aged 20–35 years. Methods: We used causal mediation analyses to estimate the total causal effect (TCE) of low education on mental health and to decompose the effect into the natural direct effect (NDE) and the natural indirect effect (NIE) through two mediators examined sequentially: employment (labour-force participation/occupation skill level) and income. Three waves of the Household, Income and Labour Dynamics in Australia (HILDA) survey (2012–14) were used to establish a temporal sequence between low education (not completing high school), mediators and mental health [the Mental Health Inventory (MHI-5)] among participants aged 20–35 years. Among those who were employed, we conducted further analyses examining the effect of job characteristics as a mediator of the relationship between low education and mental health. Results: The TCE of low education on the MHI-5 was –3.61 [95% confidence interval (CI) –5.30 to –1.92]. The NIE through labour force status and occupational skill level was –1.09 (95% CI –2.29 to 0.10) and –1.49 (95% CI –2.79 to –0.19) through both labour-force status/occupational skill level and income, corresponding to a percentage mediated of 41%. Among the employed, education had a much smaller effect on the MHI-5. Conclusions: Improving employment opportunities could reduce nearly half of the adverse effects of low education on the mental health of young people.